Media Alternatif Agar Jagung untuk Identifikasi Candida albicans - Junaedi, Winda Rachmawati; Suliati, Suliati; Mutiarawati, Diah Titik; Endarini, Lully Hanni (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
Fungal culture media is the gold standard for diagnosing candidiasis. Generally, the media used are ready-to-use preparations, as an alternative medium for the identification of Candida albicans. The carbohydrate content in the form of starch contained in the mixed corn agar media provides a source of nutrition for growth and development. The addition of Tween 80 to the mixed corn agar media under oxygen-deficient culture conditions (caused by the inoculum with a cover glass) creates an unfavorable environment and stimulates the formation of chlamydospores (a microscopic characteristic of Candida albicans). The purpose of this study was to determine the sensitivity of mixed corn agar media as an alternative medium for the identification of Candida albicans. Examination of the macroscopic characteristics of Candida albicans was carried out by inoculating a Candida albicans suspension on mixed corn agar media and cornmeal media (control). The study was conducted from December 2019 to June 2020 at the Clinical Microbiology Laboratory, Surabaya Center for Health Laboratory. Based on the results of the examination and data analysis using the Kruskal-Wallis test, the p-value was 0.368. Therefore, there were no differences in the macroscopic characteristics of Candida albicans on the three media: mixed corn agar, mixed rice agar, and cornmeal (positive control). Therefore, it can be concluded that mixed corn agar and mixed rice agar are sensitive alternative media for the identification of Candida albicans.Keywords: Candida albicans; mixed corn agar; cornmeal; macroscopic characteristicsABSTRAK Media dalam pemeriksaan kultur jamur merupakan baku emas untuk penegakan diagnosa kandidiasis. Pada umumnya media yang digunakan sudah dalam bentuk sediaan siap pakai, sebagai media alternatif untuk identifikasi Candida albicans. Kandungan karbohidrat berupa zat pati yang terdapat pada media agar jagung racikan menjadi sumber nutrisi untuk tumbuh dan berkembang. Penambahan tween 80 pada media agar jagung racikan dengan kondisi kultur kekurangan oksigen (disebabkan inoculum dengan kaca penutup) menciptakan lingkungan yang kurang baik dan merangsang pembentukan klamidospora (karakteristik mikroskopis Candida albicans). Tujuan penelitian ini adalah untuk mengetahui sensitivitas media agar jagung racikan sebagai media alternatif untuk identifikasi Candida albicans. Pemeriksaan karakteristik makroskopis Candida albicans dilakukan dengan cara menginokulasikan suspensi Candida albicans pada media agar jagung racikan, dan media cornmeal (kontrol). Penelitian dilakukan pada bulan Desember 2019 sampai  Juni 2020 di Laboratorium Mikrobiologi Klinik, Balai Besar Laboratorium Kesehatan Surabaya. Berdasarkan hasil pemeriksaan dan analisis data dengan uji Kruskal Wallis diketahui bahwa nilai p adalah 0,368. Dengan demikian, tidak ada perbedaan karakteristik makroskopis Candida albicans pada ketiga media yaitu agar jagung racikan, media agar beras racikan dan media cornmeal (kontrol positif). Dengan demikian bisa disimpulkan bahwa media agar jagung racikan dan media agar beras racikan dapat dikatakan sensitif sebagai media alternatif untuk identifikasi Candida albicans.Kata kunci: Candida albicans; media agar jagung racikan; media cornmeal; karakteristik makroskopis